(untitled) (Journal of Informatics and Mathematical Sciences, 2023)
In the present paper, we aim to establishing certain composite image formulae involving with Srivastava polynomials and generalized multiindex Bessel function. The obtained results are in the form of hypergeometric function, which are made with the help of Hadamard product. We have derived the known formulas with the help of the main results and also created some new ones.